Robotic versus laparoscopic low anterior resection for rectal cancer: a meta-analysis. Issue 1 (December 2016) - Sun, Yanlai; Xu, Huirong; Li, Zengjun; Han, Jianjun; Song, Wentao; Wang, Junwei; Xu, Zhongfa
Abstract Background The objective of this meta-analysis was to compare the clinical and oncologic outcomes of robotic low anterior resection (R-LAR) with conventional laparoscopic low anterior resection (L-LAR). Methods A search in the MEDLINE, Embase, and Ovid databases was performed for studies published before July 2014 that compared the clinical and oncologic outcomes of R-LAR and L-LAR. The methodological quality of the selected studies was assessed. Depending on statistical heterogeneity, a fixed or random effects model was used for the meta-analysis. The clinical and oncologic outcomes evaluated included operative time, estimated blood loss, length of hospital stay, rate of conversion to open surgery, post-operative complications, circumferential margin status, and number of lymph nodes collected. Results Eight studies, including 324 R-LAR cases and 268 conventional L-LAR cases, were analyzed. The meta-analysis showed that R-LAR was associated with a shorter hospital stay (mean difference (MD) = −1.03; 95 % confidence interval (CI) = −1.78, −0.28;P  = 0.007), lower conversion rate (odds ratio (OR) = 0.08; 95 % CI = 0.02, 0.31;P  = 0.0002), lower rate of circumferential margin involvement (OR = 0.5; 95 % CI = 0.25, 1.01;P  = 0.05), and lower overall complication rate (MD = 0.65; 95 % CI = 0.43, 0.99;P  = 0.04) compared with L-LAR. There was no difference in operative time (MD = 28.4; 95 % CI = −3.48, 60.27;P  = 0.08), the number of lymph nodes removed (MD = −0.63; 95 % CI = −0.78, 2.05;P  = 0.38), and days to return of bowel function (MD = −0.15; 95 % CI = −0.37, 0.06;P  = 0.17). Conclusions R-LAR was shown to be associated with a shorter hospital stay, lower conversion rate, lower rate of circumferential margin involvement, and lower overall complication rate compared with L-LAR. There were no differences in operative time, the number of lymph nodes removed, and days to return of bowel function.